The Favorable Prognostic Factors for Superior Sulcus Tumor: A Systematic Review and Meta-Analysis - Hao, Xiaohu; Wang, Zihuai; Cheng, Diou; Zhou, Jian; Chen, Nan; Pu, Qiang; Liu, Lunxu (Frontiers in Oncology, 2020)
Background: Superior sulcus tumor is a rare non-small cell lung cancer with poor prognosis. Exploring the potential prognostic factors of patients with superior sulcus tumor and adopting individualized treatment for patients with different prognostic factors is of great significance for the prolongation of patients' lives. In order to figure out the prognostic factors of the superior sulcus tumor, a meta-analysis was conducted. Method: PubMed, Embase and Web of Science databases were searched for all articles published till January 2020. The search strategy included the following terms combining of superior sulcus tumor and prognosis. Hazard ratio (HR) with associated confidential interval (CI) were evaluated for the purpose of investigating prognostic factors for superior sulcus tumor. STATA 16.0 was used for our analysis of extracted data and assessment of publication bias. Result: 17 eligible studies of 1198 patients with superior sulcus tumor were included in the meta-analysis. The studies were published between 1994 and 2018 and the patient recruitment periods ranged from 1974 to 2016. The median follow-up time ranged from 18 to 135 months. The meta-analysis indicated that lower T stage (HR, 1.63; 95% CI, 1.35-1.97), lower N stage (HR, 3.08; 95%CI:2.37-3.99), negative surgical margin (HR, 0.25; 95% CI, 0.17-0.38) and pathologic complete response (HR, 0.55; 95% CI, 0.39-0.77) were favorable prognostic factors. Conclusion: We found that T stage, N stage, surgical margin and pathologic complete response are prognostic factors for superior sulcus tumor. To reach a better long-term survival, patients with these negative prognostic factors may need more adjuvant treatment. While, more studies should be conducted to further validate these results and explore the more effective treatment.